The kinetic chain performed by high performance tennis players - Lopez de Subijana, C.; Navarro, E. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The tennis serve is one of the fundamental strokes in the development of the high performance tennis player. The aim of this study is to find the kinetic chain of two women professional tennis players' serve by means of 3D photogrammetric. The sample was 12 and 14 flat tennis serves, recorded with high speed cameras at 125 Hz. Their mean serve speeds were 38.1 m/s and 41.4 m/s. The mean of the angular velocities were 618 and 415 ‡/s at the thorax, 416 and 197 ‡/s at the pelvis; and 1404 and 1962‡/s at the internal rotation of upper arm. The kinetic energy was the biomechanical parameter considered. In both cases there was found significant energy transference between the body segments. Also, the kinetic chains found did not follow the key events of maximum angular velocities. Their parameters and timing were different between each player, in the way that they showed two models which were no compatible each other.